2021
DOI: 10.1111/lsq.12367
|View full text |Cite
|
Sign up to set email alerts
|

Attention to the COVID‐19 Pandemic on Twitter: Partisan Differences Among U.S. State Legislators

Abstract: Subnational governments in the United States have taken the lead on many aspects of the response to the COVID‐19 pandemic. Variation in government activity across states offers the opportunity to analyze responses in comparable settings. We study a common and informative activity among state officials—state legislators’ attention to the pandemic on Twitter. We find that legislators’ attention to the pandemic strongly correlates with the number of cases in the legislator’s state, the national count of new death… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…The network includes the Twitter (X) following interactions between U.S. state legislators. The data was collection by Gopal et al ( 2022) and Kim et al (2022). For this network, we only include the largest connected component of state legislators that were active on Twitter in the six months leading up to and including the insurrection at the United States Capitol on January 6, 2021.…”
Section: Descriptionmentioning
confidence: 99%
“…The network includes the Twitter (X) following interactions between U.S. state legislators. The data was collection by Gopal et al ( 2022) and Kim et al (2022). For this network, we only include the largest connected component of state legislators that were active on Twitter in the six months leading up to and including the insurrection at the United States Capitol on January 6, 2021.…”
Section: Descriptionmentioning
confidence: 99%
“…Furthermore, research has shown that state legislators exhibited partisan differences in their communication on Twitter, with Democrats emphasizing health indicators and impacts with respect to COVID‐19, while Republicans emphasized business impacts of COVID‐19 and reopening the economy (Kim et al. 2021). Gardner and Russell (2022) also show that among senators, Republicans were more likely to tweet positively about economic recovery, while Democrats tweeted negatively about failures of the government in addressing the pandemic.…”
Section: Gender Differences In Congressional Communication and Behaviormentioning
confidence: 99%
“…Since Republican politicians, including President Trump, downplayed the severity of COVID-19 comparing it to the flu and undercutting public health officials' recommendations, while Democratic officials encouraged the public to follow the recommendations of the public health officials and Centers for Disease Control (CDC) (Kushner Gadarian et al 2021), we suspect that there will be clear differences in the number of tweets sent by the two parties. Furthermore, research has shown that state legislators exhibited partisan differences in their communication on Twitter, with Democrats emphasizing health indicators and impacts with respect to COVID-19, while Republicans emphasized business impacts of COVID-19 and reopening the economy (Kim et al 2021). Gardner and Russell (2022) also show that among senators, Republicans were more likely to tweet positively about economic recovery, while Democrats tweeted negatively about failures of the government in addressing the pandemic.…”
Section: Gender Differences In Congressional Communication and Behaviormentioning
confidence: 99%
“…As the central body responsible for overseeing pandemic response and preparedness, state and local officials had particular incentive to provide non-partisan information and updates on the pandemic in their communications (Zahry et al, 2023). Indeed, state-level officials have been found to have tweeted frequently about the pandemic, especially in its earliest stages (Gong & Ye, 2021), focusing primarily on health and business-related topics (Kim et al, 2022). This local focus may mean that state and local officials were less attached to polarized rhetorical trends at the national level and therefore less likely to discuss COVID-19 in a polarizing fashion.…”
Section: Polarizing Rhetoricmentioning
confidence: 99%